Els postulats de la filologia romànica internacional sobre l'origen, la identitat i el nom de la llengua catalana (1806-1906). - MARTÍ-BADIA, ADRIÀ (Scripta, 2019)
This paper analyses the postulates of the non-Catalan-speaking Romanists about the origin, the identity and the name of the Catalan language between 1806 and 1906. Romance philology emerges in the 19th century and scholars started to categorize and study the different romance languages. Progressively, during this period, Romanists take into consideration the Catalan language and make statements about its origin --shared with the Occitan language or independent from the beginning--, its identity --subordinated to Occitan or autonomous as the other romance languages-- and the name with which the language should be mentioned.